Beyond mineralisation: metabolic functions for matrix mineralisation regulators. Issue 2 (May 2020) - Roberts, Fiona; Markby, Greg; Dillon, Scott; Farquharson, Colin; MacRae, Vicky E
Abstract : The physiological mineralisation of skeletal tissues, as well as the pathological mineralisation of soft tissues involves a fine balance between regulators that either promote or inhibit the process. In recent years, several studies have advocated a non-skeletal role for some of these mineralisation regulators in a range of human diseases, including diabetes, cardiovascular disease, obesity and neurodegenerative disease. This is an emerging area of interest and the functional roles and mechanisms of action of these various endocrine factors, phosphatases and phosphodiesterase's in important pathologies are the focus of this review. Mechanistic insight of the pathways through which these acknowledged regulators of skeletal mineralisation act beyond the skeleton has the potential to identify druggable targets for commonly experienced morbidities, notably those related to metabolism and metabolic syndrome.